1998
DOI: 10.1021/bi981286b
|View full text |Cite
|
Sign up to set email alerts
|

Intrastrand Cross-Linked Actin between Gln-41 and Cys-374. III. Inhibition of Motion and Force Generation with Myosin

Abstract: Structural and functional properties of intrastrand, ANP (N-(4-azido-2-nitrophenyl)-putrescine) cross-linked actin filaments, between Gln-41 and Cys-374 on adjacent monomers, were examined for several preparations of such actin. Extensively cross-linked F-actin (with 12% un-cross-linked monomers) lost at 60 degrees C the ability to activate myosin ATPase at a 100-fold slower rate and unfolded in CD melting experiments at a temperature higher by 11 degrees C than the un-cross-linked actin. Electron microscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 54 publications
4
64
0
Order By: Relevance
“…Previously, we reported that an actin longitudinal dimer can be stabilized by cross-linking the Gln-41 and Cys-374 residues of two adjacent actin protomers with a heterobifunctional photo-activated reagent, ANP (21,31,36). The purified ANP cross-linked dimers can be readily reassembled into filaments (in the presence of Mg 2ϩ ).…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported that an actin longitudinal dimer can be stabilized by cross-linking the Gln-41 and Cys-374 residues of two adjacent actin protomers with a heterobifunctional photo-activated reagent, ANP (21,31,36). The purified ANP cross-linked dimers can be readily reassembled into filaments (in the presence of Mg 2ϩ ).…”
Section: Results and Analysismentioning
confidence: 99%
“…The longitudinal dimer of rabbit skeletal actin was prepared by cross-linking Gln-41 and Cys-374 residues of two adjacent actin protomers with a photo-activated heterobifunctional reagent N-(4-azido-2-nitrophenyl) putrescine (ANP), as described earlier (21,31). To decrease the amount of higher-order actin oligomers, cross-linking was carried out with copolymers made from equal amounts of ANP-labeled (by means of transglutaminase reaction) and unlabeled actin.…”
Section: Methodsmentioning
confidence: 99%
“…Rather than forming true microtubules, monomer aggregates could induce the formation of microtubule bundles, not necessarily formed only by covalent aggregates of tubulin but also by monomeric tubulin "entrapped" into the aggregates. [39,40]. In addition, the TGase-mediated intramolecular cross-linking between Gln 41 and Lys 50 disturbed the structure of G-actin but apparently had small effects on actin polymerization and on myosin interaction [32] or could even activate the ATPase activity of myosin subfragment 1 [9].…”
Section: Pollen Tgase Affects the Polymerization Dynamic Of Microtubulesmentioning
confidence: 99%
“…The interface through which they interact is the longitudinal interface. While variable twist angles of filaments have been well documented (Egelman et al, 1982;Stokes & DeRosier, 1987;Kim, Bobkova et al, 1998;Galkin et al, 2001), in general the two protofilaments in the F-actin filament are staggered so that two adjacent monomers from different protofilaments are related to each other by a rotation of about $166…”
Section: Introductionmentioning
confidence: 99%
“…Defined oligomers of actin can be obtained by limited cross-linking in the filamentous state, followed by depolymerization and purification. Chemical strategies have been developed for specific cross-linking in either the longitudinal or lateral directions Kim, Bobkova et al, 1998;Kim, Phillips et al, 1998;Knight & Offer, 1978). The first structural study of a cross-linked actin oligomer was of a trimer held together by two lateral cross-links, with polymerization blocked by a gelsolin segment 1 (GS1) bound to each protomer (Dawson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%